2017
DOI: 10.1016/j.ijms.2017.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Selective reagent ion-time of flight-mass spectrometry study of six common monoterpenes

Abstract: a b s t r a c tOne of the most common volatile organic compounds (VOCs) group is monoterpenes. Monoterpenes share the molecular formula C 10 H 16 , they are usually cyclic and have a pleasant smell. The most common monoterpenes are limonene (present in citrus fruits) and ␣-pinene (present in conifers' resin). Different monoterpenes have different chemical, biological and ecological properties thus it is experimentally very important to be able to differentiate between them in real time. Real time instruments s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…Here we record only ion signals, which are detected with relative intensities >1%. Other fragments reported in the literature for H 3 O + chemical ionization using PTR-MS instruments (Wang et al, 2003; Schoon et al, 2004; Tani et al, 2004; Materić et al, 2017) have not been observed. This could be explained by the smaller amount of transferred internal energy using NH4+ instead of H 3 O + as reagent ion.…”
Section: Resultsmentioning
confidence: 88%
“…Here we record only ion signals, which are detected with relative intensities >1%. Other fragments reported in the literature for H 3 O + chemical ionization using PTR-MS instruments (Wang et al, 2003; Schoon et al, 2004; Tani et al, 2004; Materić et al, 2017) have not been observed. This could be explained by the smaller amount of transferred internal energy using NH4+ instead of H 3 O + as reagent ion.…”
Section: Resultsmentioning
confidence: 88%
“…This can be achieved by (i) changing the reagent ion, examples for which have been presented in the literature for explosives (Sulzer et al, 2013; Agarwal et al, 2014), or psychoactive substances (Acton et al, 2014; Lanza et al, 2015), and/or (ii) the collisional processes in the drift tube through changing the reduced electric field. Changes in the reduced electric field (the ratio of the electric field strength, E , to the gas number density, N , in the drift tube) to alter the product ion distributions have been demonstrated in the areas of homeland security, e.g., detection of chemical warfare agents (Petersson et al, 2009), explosives (Mayhew et al, 2010; Sulzer et al, 2012, 2013), and rape drugs (Jürschik et al, 2012), and in environmental science, e.g., the identification of monoterpenes (Materić et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that NO + reacts with monoterpenes via charge transfer and in most cases the molecular cation C 10 H 16 +• at m/z 136 is the dominant product ion. [9][10][11] Thus it is necessary to account for about 25% of NO + present in the DTR to obtain the correct data for product ion distribution for reaction with C 8 H 8 +• (and possibly (C 8 H 8 ) 2 +• ). Fortunately, it is easy to do this from the ion-molecule reaction kinetics when the reaction rate coefficient k and the reaction time t r are known.…”
Section: Correction Due To Presence Of No +mentioning
confidence: 99%
“…Measurements of the total concentration of monoterpenes in air can be achieved by chemical ionization mass spectrometry, CIMS, techniques based on ion‐molecule reactions in flow/drift tube reactors, where ionization of the neutral monoterpene molecules is usually accomplished by gas‐phase reactions with H 3 O + or NO + reagent ions taking place at air sample pressures <2 mbar as realized in proton transfer reaction mass spectrometry, PTR‐MS, and selected ion flow tube mass spectrometry, SIFT‐MS . This allows real‐time quantification of atmospheric monoterpenes at concentration levels down to 1 part per billion per volume, ppbv, and lower.…”
Section: Introductionmentioning
confidence: 99%